Pengembangan Pengelolaan Dana Zakat di LAZISMU Sebagai Peningkatan Kualitas Organisasi PCIM (Pimpinan Cabang Istimewa Malaysia) - Ghozali, Mohammad; Abdul Aziz, Muhammad; Rachmawati, Andini; Reyhan, Muhammad; Zulhuda, Sonny (Universitas KH. Mukhtar Syafaat (UIMSYA), 2024)
How important essence is in the Muhammadiyah movement, zakat and the generous dimension are important, strategic and effective agendas. Lazismu is the leader. Zakat is one of the pillars of Islam which guides Muslims in implementing it. Zakat is an activity to cleanse oneself of possessions to carry out social responsibilities. Zakat management has different forms of supervision, so that sometimes there are different perceptions about the zakat operating system, where zakat can change it towards improving the economy. Furthermore, the data collected will become part of the large zakat data which can lead to improvements in the people's economy. The problem that occurs in PCIM Malaysia is that the zakat collection that has been carried out is still not significant in relation to the residents of Kampung Baru, Kuala Lumpur. This is shown because the level of community involvement in the zakat management system at PCIM is not optimal. The meeting, which lasted for two hours, discussed various aspects related to zakat in the Muhammadiyah Association and also aspects of digitalization in the management, communication and distribution of zakat funds. This activity uses an advanced approach to the community through broadcasting or preaching to the residents of Kampung Baru, Kuala Lumpur. It is hoped that this community service program will provide awareness to people who already have the obligation to pay zakat so that the quantity of zakat collection in PCIM will increase.